ANALISIS PELAKSANAAN WEBINAR SEBAGAI UPAYA UNTUK MENINGKATKAN PRESTASI AKADEMIS MAHASISWA - Gusti, Utari akhir (Yayasan Indonesia Bermutu, 2024)
During and after the Covid-19 pandemic, Webinar or Web-based seminars have become trending. However, not much research has been conducted analyzing how webinars are implemented as an effort to improve student academic achievement. The research approach is qualitative with a phenomenological approach using data collection techniques by distributing questionnaires and semi-structured interviews. The results of this research describe the results of a webinar attended by students throughout Indonesia to discuss motivation and performance improvement with representatives from each island. The analysis results show that 54.20% of participants took part in webinars 3-4 times a week, this shows high enthusiasm for this activity. Information regarding the webinar was mostly obtained via WhatsApp (67.50%), which shows the effectiveness of social media as a means of information. Motivations for participating in webinars vary, from gaining insight to being motivated to appear. In short, webinars can be an important element in improving student performance, building skills and knowledge, and supporting academic and non-academic growth. Factors such as exposure to high-achieving students, participation in webinars, and parental support were identified as mutually reinforcing factors in helping students achieve higher grades